1952
DOI: 10.1111/j.1469-1809.1952.tb02504.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fitting of the Positive Binomial Distribution When Both Parameters Are Estimated From the Sample

Abstract: 1. The positive binomial distribution P ( z ) = pXqn-" is usually fitted to samples (consisting of, say, N sampling units) with n known. When the estimation of both n and p must be done from the sample (e.g. Hoel, 1947;Skellam, 1948) this can be efficiently done by putting Z = , 2 ( p = np) and obtaining n as the root of the maximum-likelihood equation: 0 N , c x=j+l = 0 (Haldane, 1941; Fisher, 1941)R-1 j=o 6 -j by iteration (then $ can be obtained as Z/6) (R = max. {xi}, N , = sample frequency of z). This est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Binet 1953;Fisher 1941;and Haldane 1941 It should be emphasized that (3.2) is the result of the old method existing in the literature while (3.1) comes from the method proposed here. We now compare the two methods by considering a numerical example (Binet 1953) If we assume a binomial (N,6) distribution (Binet 1953), the moment estimate of N, that is the nearest integer to X2/(X -S2), iS 12, where S2 = (X, -)2 (n -1) is the sample variance. In order to obtain the MLE of N, Binet (1953) evaluated the likelihood function for N = 11, 12, and 13, obtained the largest value at N = 12, and concluded that the MLE for this data is 12.…”
Section: Some Applicationsmentioning
confidence: 91%
See 3 more Smart Citations
“…Binet 1953;Fisher 1941;and Haldane 1941 It should be emphasized that (3.2) is the result of the old method existing in the literature while (3.1) comes from the method proposed here. We now compare the two methods by considering a numerical example (Binet 1953) If we assume a binomial (N,6) distribution (Binet 1953), the moment estimate of N, that is the nearest integer to X2/(X -S2), iS 12, where S2 = (X, -)2 (n -1) is the sample variance. In order to obtain the MLE of N, Binet (1953) evaluated the likelihood function for N = 11, 12, and 13, obtained the largest value at N = 12, and concluded that the MLE for this data is 12.…”
Section: Some Applicationsmentioning
confidence: 91%
“…It is clear that L*(N) is a decreasing function of N for N -7, so that Binet's (1953) calculations were in error. The method proposed here does not require evaluation of the likelihood function, and a hand calculator is enough to find the rough range for the root of (3.1) which provides the MLE of N.…”
Section: Some Applicationsmentioning
confidence: 97%
See 2 more Smart Citations
“…Related work on the estimation of N in the Binomial problem has been undertaken by Binet (1954), who discussed the relative appropriateness of Binomial, Negative Binomial, and Poisson models; Feldman and Fox (1968), Draper and Guttman (1971), Kahn (1987), Raferty (1988), and Aitkin ( 1992), who suggested Bayesian approaches to inference; DeRiggi (1978), who described the shape of the likelihood function and its ramifications; Casella (1986) and Aitkin and Stasinopoulos (1 989), who discussed several issues of stability; and Blumenthal and Dahiya (198 1) and Aitkin (199 l), who reviewed previous work on the problem. Aitkin's review, part of a much more general account of Bayesian inference, is particularly illuminating in terms of the light that it sheds on the effect of different prior p densities on the integrated likelihood and its interpretations.…”
Section: Introductionmentioning
confidence: 99%